Аssessment of the ecological condition of the Western Bug river basin according to the macrophyte index for rivers (MIR) - Nekos, Alla N.; Boіaryn, Mariіa V.; Lugowska, Maria; Tsos, Oksana O.; Netrobchuk, Iryna M. (My University, 2021)
Introduction. To restore and preserve the optimal ecological status of the Western Bug river basin, it is necessary to adhere to the strategic principles of environmental management, and since the river is transboundary and tributary basins are located in Ukraine and Poland, it is important to determine the ecological status of small rivers. In the territory of the Volyn region, the rivers-tributaries Luha and Studyanka are most affected by anthropogenic impact. An ecological assessment of water quality based on the condition of macrophytes is given, as macrophytes llow to determine the degree of surface water degradation, first of all, in terms of their trophic status. The purpose of article. The purpose of article aims to assess the ecological status of the rivers of the Western Bug river basin using bioindication methods and determination of the Macrophyte Index for Rivers (MIR). Methods. Research methods are expeditionary, methods of mathematical statistics end bioindication methods and determination of the Macrophyte Index for Rivers (MIR). Results. To determine the ecological status of the rivers of the Western Bug basin and to conduct research, three test sites with a length of at least 100 m were laid on two tributaries of the first order - the rivers Luha and Studyanka. To determine the MIR (Macrophyte Index for Rivers) in the test riverbed areas, 42 indicator species of macrophytes were selected, of which 1 species belongs to the division Polipodiophyta and Equisetophyta, 40 species to the division Magnoliophyta, of which 15 belong to the class Magnoliopsida, and 25 belong to the class Liliopsida. According to the classification of the MIR indicator, to determine the ecological status, the rivers Luha and Studyanka belong to lowland watercourses, with the type of macrophytes - M-VIII (organic rivers). As a result of the calculated Macrophyte Index for Rivers (MIR), it was established (Table 4) that the water quality in the Luha river in test site 1 (Zavydiv village) has a good ecological status, MIR is 39,0; and test site 2 (Volodymyr-Volynskyi city) has a satisfactory or moderate ecological status, MIR is 31,56; in the river Studyanka, the test site 3 (Ustyluh town) has a satisfactory or moderate ecological condition, MIR is 28,31. Conclusions. According to the ecological status of rivers determined by the Macrophyte Index for Rivers (MIR), it is established that the waters of the Luha and Studyanka rivers have a satisfactory or moderate ecological condition. This suggests that the research conducted on test sites and calculations of the Macrophyte Index for Rivers (MIR) are identical and fully reflect the ecological status of the rivers Luha and Studyanka determined by hydrochemical parameters, which allows the use of this research algorithm for other rivers in the Western Bug river basin and is promising during research on other rivers of Ukraine.
Оцінка екологічного стану річок басейну Західного Бугу за індексом макрофітів (MIR)
Keywords: river; bioindication; macrophytes; ecological condition of rivers; macrophyte index; water quality classes; ecological assessment of water quality; 556.51:502.51(477)